The Relationship Between Chronic Kidney Disease and the Severity of Pruritus in Patients Undergoing Hemodialysis at Royal Prima General Hospital in Medan - Popy Fazriani; Ade Arhamni; Lisdawaty Siregar (International Journal of Health and Pharmaceutical (IJHP), 2025)
Chronic kidney disease-associated pruritus represents a prevalent complication that significantly impairs hemodialysis patient quality of life. This study examined the relationship between hemodialysis duration and uremic pruritus severity. An analytical cross-sectional design enrolled 34 chronic kidney disease patients receiving maintenance hemodialysis at Royal Prima General Hospital, Medan. Data collection utilized questionnaires and medical records; purposive sampling identified meeting participants inclusion criteria. Univariate analysis described demographic and clinical characteristics using frequency distributions. Bivariate chi-square analysis tested associations between hemodialysis duration (categorized as less than 6 to 12 months, 13 to 24 months, and greater than 24 months) and pruritus severity (mild, moderate, severe) using IBM SPSS Statistics software. Results demonstrated a highly significant association between dialysis duration and pruritus severity (χ² = 17.661, p = 0.000), with severe pruritus occurring in 0% of early-stage dialysis patients, 16.7% of intermediate-duration patients, and 82.4% of long-term recipients. Extended hemodialysis exposure correlates directly with progressive pruritus escalation through cumulative uremic toxin accumulation and inflammatory activation. These findings substantially systematic pruritus screening and multimodal management implementation for all dialysis patients, particularly targeting long-term recipients experiencing substantial symptom burden.